2000
DOI: 10.1093/jnen/59.6.504
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Losses in Neurofibromatosis 2-Associated Meningiomas

Abstract: More than 50% of patients with neurofibromatosis 2 (NF2) develop meningiomas. Recently, a higher proliferative activity, more mitotic figures, and greater nuclear pleomorphism have been described for NF2-associated meningiomas compared with sporadic ones. To analyze whether such histological differences could reflect underlying genetic differences, we examined 30 meningiomas from 22 NF2 patients for allelic losses on those chromosome arms that are frequently affected by deletions in sporadic meningiomas. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 32 publications
2
24
0
1
Order By: Relevance
“…Of note, this sample is the only one in the NF2-nonmutated group that harbors 22q loss; thus, this sample might indeed have NF2 inactivation through, for example, epigenetic mechanisms. In the literature, the NF2 status of meningioma samples is seldom determined, but review of literature clustering samples according to their 22q status also finds an association between 22q loss and FAL in the meningiomas studied (14,35,36,(46)(47)(48). These studies are in agreement with our finding that NF2 inactivation in meningiomas is associated with greater chromosome instability.…”
Section: Nf2 Loss Is Associated With Chromosome Instability In Progresupporting
confidence: 89%
“…Of note, this sample is the only one in the NF2-nonmutated group that harbors 22q loss; thus, this sample might indeed have NF2 inactivation through, for example, epigenetic mechanisms. In the literature, the NF2 status of meningioma samples is seldom determined, but review of literature clustering samples according to their 22q status also finds an association between 22q loss and FAL in the meningiomas studied (14,35,36,(46)(47)(48). These studies are in agreement with our finding that NF2 inactivation in meningiomas is associated with greater chromosome instability.…”
Section: Nf2 Loss Is Associated With Chromosome Instability In Progresupporting
confidence: 89%
“…Previous studies in sporadic meningiomas show a high frequency (44 -100%) of LOH on chromosome 22q12 at NF2 gene locus (35, 39 -44), and patients with NF2 develop menigiomas that have a high frequency of NF2 gene LOH (49). Our results from allelotyping of 22q12 in the MEN 1-associated meningioma show that there is no LOH on chromosome 22q12 in the region of the NF2 gene.…”
Section: Discussionsupporting
confidence: 45%
“…Previous studies have shown a high frequency of LOH on chromosome 1p LOH (28 -57%) and at 22q12 (44 -100%) at the NF2 tumor suppressor gene locus (28, 35, 39 -48) in sporadic meningiomas and in NF2-associated meningiomas (49), and their presence correlates with an aggressive growth pattern, tumor site, high histological grade, and decreased recurrencefree survival (40, 41, 44 -46). To assess these genetic alterations (NF2 and 1p) as well as possible LOH at the MEN1 locus on chromosome 11q13 in this MEN 1-associated meningioma, each of these regions was examined with polymorphic microsatellite markers (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of a sex Table 2 Correlation Between the Numerical Abnormalities Observed for Chromosomes 1,9,10,11,14,15,17,22 chromosome in somatic cells is a relatively frequent agerelated phenomenon, usually including loss of the Y chromosome in bone marrow cells from older male individuals (40). However, it was never found at the high frequencies reported here.…”
Section: Discussionmentioning
confidence: 99%
“…From the reported individual abnormalities, the monosomy 22/22q -deletion is, by far, the most frequent aberration detected in typical meningiomas (2,7,12,14,17,19 -21). Other chromosome abnormalities described as relatively frequent in these tumors include loss/deletion of chromosomes 1p, 14q, 10q, and the sexual chromosomes (22)(23)(24)(25)(26)(27). In contrast, chromosome gains and complex karyotypes are usu-ally found in a low proportion of cases.…”
mentioning
confidence: 99%